Performance simulation of Modenas 110cc 4-stroke motorcycle engine - Amirul Amir, Abd Jamil (2009)
This thesis present about the effect of compression ratio to the Modenas 110cc four stroke motorcycle engine. The objective of this project is to increase the performance of the engine. Using GT Power engine simulation software, the original parameter will be check and change to get the highest performance. The changes of the performance will be compared before it is choose. The percentages change will be calculated and compared with the original parameter. As the conclusion, the compression ratio will affect the engine performance and fuel consumption of the engine.